Does Crop Improvement reduce Agricultural Expansion? Brief Number 40 - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2012)
This brief is based on the paper by Stevenson, J., et al. (2011) Agricultural technology, global land use and deforestation: a review and new estimates of the impact of crop research. In: CGIAR Independent Science and Partnership Council. 2011. Measuring the environmental impacts of agricultural research: Theory and applications to CGIAR research.